RUDAKI’S PHILOSOPHICAL VIEWS IN HIS WORKS - Azimov, Adiz Abdullaevich (Educational Research in Universal Sciences, 2023)
The article analyzes the philosophical and ethical views of the great poet Abu Abdullah Rudakiy Samarkandiy, Rudakiy’s worldview was formed during the period of the power of the Samanid state, when, thanks to peace and relative calm, agriculture, crafts, trade, literature, science and philosophy rapidly developed. Rudaki constantly calls for action, work, acquisition of knowledge, life experience: In life we gain experience - life teaches us, gives advice, To avoid accidental troubles on the road of life.